Les organisations de défense des droits de l’Homme dans la formule politique tunisienne : acteurs de l’opposition ou faire-valoir du régime ? - Larbi Chouikha; Eric Gobe (L’Année du Maghreb)
In Tunisia, the critical concept that allows assessment of relations between the government and human rights organizations and opposition groups active in their midst is the element of compromise. Some opposition members of human rights organisations actively seek areas of conflict with the government. The contradiction between the search for a compromise at any cost and the affirmation of an opposing position explains how it is that the only legalized human rights association constitutes the locus of confrontation between political actors, and how the national authority seeks to transform the organisation into a proxy for its own rhetoric on human rights.